Desenvolvimento de um novo nanomaterial incorporado com bixina: uma abordagem sustentável para remoção de corantes em matrizes aquosas - Junielly Tomaz Domingues (2018)
An environmentally safe technology was developed for the removal of brilliant green and methylene blue dyes. A new nanostructured adsorbent material composed of polycaprolactone polymer (8.00% w/v) and bixin, at a ratio of 10.0% (w/v) in relation to the polymer and the metallic support was manufactured using an electrospinning technical and it was applied to the removal of dyes. The best sorption condition was obtained evaluating the deposition nanofibers time on the support (20, 40, 60, 70, 80 e 120 minutes), the support dimensions deposited with nanofibers (2.6 x 1.4, 2.6 x 2.0, 2.6 x 2.6, 2.6 x 3.2 e 2.6 x 3.8 cm x cm), the temperature during the adsorption process (15.0; 25.0; 35.0 e 45.0 ºC), the pH reactive medium (2.00; 4.00; 6.00; 8.00 e 10.0), adsorptionkinect and adsorption isotherm. The highest removal percentage of dyes was obtained using solutions at the concentration of 20.0 mg kg-1, pH = 6.00 at room temperature (25.0 ºC) applying the PCL nanofibers incorporated with bixin deposited on each face of the stainless-steel holder for 80 minutes. An approximate removal to brilliant green andmethylene blue obtained was equal to 96.0% and 70.0%, respectively. The adsorption kinect observed was fast, reaching the adsorption equilibrium in 2 hours of analyte contact with the adsorbent and the kinect model that best adjusted to the date was pseudo-second order model. The dyes sorption showed to be influenced by the presence of some salts, causing possible modifications in the stability of the material and suggesting the process occurs by ion exchange mechanism. In addition, PCL and bixin nanofibers were applied for dye removal in textile effluents, which did not favor sorption, in matrices receiving the raw textile effluent and in fish-breeding and shrimp-breeding water, in which thematerial was shown to be a promising adsorbent with interesting characteristics, such as its lack of toxicity.